Estimating dynamic panel models: Backing out the Nickell bias - Jerry A. Hausman; Maxim L. Pinkovskiy (Federal Reserve Bank of New York, 2017)
We propose a novel estimator for the dynamic panel model, which solves the failure of strict exogeneity by calculating the bias in the first-order conditions as a function of the autoregressive parameter and solving the resulting equation. We show that this estimator performs well as compared with approaches in current use. We also propose a general method for including predetermined variables in fixed-effects panel regressions that appears to perform well.
Keywords: C2; C23; C26; 330; dynamic panel data; bias correction; econometrics